Agronomic and physiological responses of rice to sodium treatments and high CO2 - Vieira, Daniel Amorim (2021)
The increase in carbon dioxide (CO2) emissions mainly affects plants that present the C3 pathway, contributing to the reduction of photorespiration and, consequently, reduction of nitrogen (N) assimilation. An element that can reduce the effects of increased CO2 on N assimilation is sodium (Na+) acting as a cofactor in pyruvate transport, having a direct role in the regeneration of Phosphoenolpyruvate carboxylase (PEPC). Rice was chosen for the job because of its great socio-economic importance and also because of the increase in demand for rice in the coming years. In this context, we set up two experiments with the aim of investigating how Na+ availability can affect the growth and production of tropical upland rice lines. The objective of the first experiment was to select lines with greater tolerance to salinity, and the line that showed the best responses was used in the second experiment, which aimed to evaluate the influence of sodium on photosynthesis modeling and rice grain yield under high CO2. The first experiment was carried out in a greenhouse with a completely randomized block design (RBD) and a double factorial scheme: the first factor being the ten upland rice lines and the second variation factor the NaCl concentrations (0, 3, 15 and 45 mmol per L) in 5 repetitions, one individual per experimental unit, totaling 200 plots. The characteristics evaluated were: total chlorophyll content, gas exchange, shoot and root dry matter content, phenology and production variables. For the second experiment, conducted in an open-top chamber, the experimental design was completely randomized, with treatments: 0 mmol L-1 NaCl and 400 μmol mol-1 CO2 (C1S1); 3 mmol L-1 of NaCl and 400 μmol mol-1 of CO2 (C1S2); 0 mmol L-1 of NaCl and 700 μmol mol-1 of CO2 (C2S1) and 3 mmol L-1 of NaCl and 700 μmol mol-1 of CO2 (C2S2). In the first experiment, at the end of the cycle, using the grain yield per plant (GWP) as an indicator of plant performance under salinity, L6, L7 and L8 showed the best results. L6 had the highest GWP, while L7 and L8 had the smallest reduction in GWP with increases in NaCl, these lines are recommended for further testing to assess the impact of salt stress on rice crops. In the second experiment it was possible to prove the effects of NaCl under high CO2 conditions on photosynthetic processes, under 2% oxygen conditions under C2S2 treatment for variable J was greater than C2S1. The C1S2 treatment increased J / Vcmax under conditions of 21% oxygen when compared to the control treatment, however, with the supply of the dose of NaCl under high CO2 conditions, there was a decrease in grain production under these conditions. The dose of NaCl and the elevation of CO2 alone were beneficial to the plant in relation to photosynthesis and grain yield for the rainfed line CMG 2085.